The Impact of Parenting Styles Based on the Health Belief Model on School-Age Children's Personal Hygiene in the Bangka Region - Akhiat; Dudella Desnani Firman Yasin; Sammy Lazuardi; Moh Wildan; Chitra Fraghini (KHD-Production, 2024)
This study explores the impact of parenting styles, grounded in the Health Belief Model (HBM), on the personal hygiene practices of school-aged children in the Bangka region of Indonesia. Personal hygiene is critical for preventing diseases, particularly in children aged 6-12, who are at higher risk of exposure to disease-causing environments such as schools. Using a cross-sectional design, the study collected data from 80 parents and children through validated questionnaires, examining how different parenting styles—authoritarian, permissive, and democratic—affect children’s hygiene habits. The results indicate a strong correlation between parenting style and children's hygiene practices, with authoritarian parenting being the most prevalent (40%) and showing the highest adherence to hygiene routines. Additionally, the study found a significant positive relationship between parents' awareness of hygiene-related health risks and their children’s hygiene behaviors. The findings suggest that parental engagement and health beliefs play a crucial role in shaping children’s hygiene habits. These results have important implications for public health policies and parental education programs, emphasizing the need for targeted interventions that improve parental health literacy and promote balanced parenting styles to ensure long-term hygiene habits in children. The study calls for further research into culturally appropriate educational strategies that support parental involvement in promoting child health in regions with high incidences of hygiene-related diseases.